Interlocking mortarless load bearing building block systems / Putra Block - Abdul Kadir, Mohd Razali; Abang Ali, Abang Abdullah; Jaafar, Mohd Saleh; Abdul Samad, Abdul Aziz; Ibrahim, Rahinah (2005)
The present invention relates to an interlocking modular block system for mortarless wall assembly. A plurality of blocks are laid up in courses in a staggered relationship in which three different block configurations are provided, namely stretcher, corner and half block units. The stretcher and corner blocks have lengths at least one and a half times the width, and the half block has the same width and a length which is half the length of the stretcher and corner blocks. The invention offers a simple and fast construction procedure, even when using unskilled labor.